Answer:
sorry if im wrong i think wrong numbers. plz check
Step-by-step explanation:
The center of dilation of the question is (-4,-3) .
let say that
x0=-4
y0=-3
Label the image A'B'C'
The new coordinate would be
A(-4,-1)
x=4
y=-1
x'=x0+ 2(x - x0)
x'= -4+ 2(-4 +4)
x'=-4
y'=y0+ 2(y - y0)
y'= -3+ 2(-1 +3)
y'=-3 +4= 1
______________________________
B(-4,-3)
x=-4
y=-3
x'=x0+ 2(x - x0)
x'= -4+ 2(-4 +4)
x'=-4
y'=y0+ 2(y - y0)
y'= -3+ 2(-3 +3)
y'=-3
______________________________
C(-1,-3)
x=-1
y=-3
x'=x0+ 2(x - x0)
x'= -4+ 2(-1 +4)
x'=-4 +6= 2
y'=y0+ 2(y - y0)
y'= -3+ 2(-3 +3)
y'=-3
A'(-4,1)
B'(-4,-3)
C'(2,-3)
Answer:
- 48
Step-by-step explanation:
If you want to learn more about this concept, it's called composition of functions.
First, you plug in g(x) as if it were x into f(x).
f(g(x))= -5 (1/2x + 4) + 2
= -5/2x - 20 + 2
= -5/2x - 18
Then, plug in the value given, as x.
= -5/2 (12) - 18
= -30 - 18
= - 48
I hope this helped!
Answer:
Holding your breath is called static Apnea and a common person can't hold their breath for long. If a person holds their breath for long and dies because of it, it may be called lack of breath or lack of respiration.
a) Acceleration is the derivative of velocity. By the fundamental theorem of calculus,
so that
b) We get the displacement by integrating the velocity function like above. Assume the object starts at the origin, so that its initial position is . Then its displacement over the time interval [0, 3] is
c) The total distance traveled is the integral of the absolute value of the velocity function:
for and for , so we split the integral into two as
9514 1404 393
Answer:
A
Step-by-step explanation:
Attached is a copy of the figure with some of the clutter removed. The congruent angles marked with a single arc, and the parallel lines are given.
The angles marked with a double arc are congruent because they are alternate interior angles where transversal XZ crosses parallel lines XW and YZ. Of course, side XZ is congruent to itself.
Hence we have two angles and a side not between them that are congruent. We can declare ∆XWZ ≅ ∆ZYX by the AAS postulate. (choice A)